E2 Proteins of High Risk Human Papillomaviruses Down-Modulate STING and IFN-κ Transcription in Keratinocytes - Sunthamala, Nuchsupha (Public Library of Science, 2014)
In the early stages of human papillomavirus (HPV) infection, the viral proteins elicit specific immune responses that can participate to regression of ano-genital lesions. HPV E6 protein for instance can reduce type I interferon (IFN) including IFN-κ that is involved in immune evasion and HPV persistence. To evaluate the role of E2 protein in innate immunity in HPV16-associated cervical lesions, genome-wide expression profiling of human primary keratinocytes (HPK) transduced by HPV16 E2 was investigated using microarrays and innate immunity associated genes were specifically analyzed. The analyses showed that the expression of 779 genes was modulated by HPV16E2 and 92 of them were genes associated with innate immunity. Notably IFN-κ and STING were suppressed in HPK expressing the E2 proteins of HPV16 or HPV18 and the trans-activation amino-terminal domain of E2 was involved in the suppressive effect. The relationship between STING, IFN-κ and interferon stimulated genes (ISGs) in HPK was confirmed by gene silencing and real time PCR. The expression of STING and IFN-κ were further determined in clinical specimens by real time PCR. STING and IFN-κ were down-modulated in HPV positive low grade squamous intraepithelial lesions compared with HPV negative controls. This study demonstrates that E2 proteins of high risk HPV reduce STING and IFN-κ transcription and its downstream target genes that might be an immune evasion mechanism involved in HPV persistence and cervical cancer development.